2000
DOI: 10.1086/317880
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Massive Black Hole at the Center of the Superbubble in M82

Abstract: We performed CO (1-0), CO (1-0), and HCN (1-0) interferometric observations of the central region 12 13 (about 450 pc in radius) of M82 with the Nobeyama Millimeter Array and have successfully imaged a molecular superbubble and spurs. The center of the superbubble is clearly shifted from the nucleus by 140 pc. This position is close to that of the massive black hole (BH) of տ460 M and the 2.2 mm secondary peak (a luminous , supergiant-dominated cluster), which strongly suggests that these objects may be re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 31 publications
10
91
0
Order By: Relevance
“…3.2.4) are quite similar. A more recent study by Weiß et al (1999) discovered an additional CO feature in M 82 that is suggested to be a superbubble driven by a starburst in its center (Matsushita et al 2000), similar to the wildfire mode proposed by Alonso-Herrero et al (2001) for NGC 1614.…”
Section: Comparing Ngc 1614 With Galaxies With Nuclear Molecular Ringssupporting
confidence: 56%
“…3.2.4) are quite similar. A more recent study by Weiß et al (1999) discovered an additional CO feature in M 82 that is suggested to be a superbubble driven by a starburst in its center (Matsushita et al 2000), similar to the wildfire mode proposed by Alonso-Herrero et al (2001) for NGC 1614.…”
Section: Comparing Ngc 1614 With Galaxies With Nuclear Molecular Ringssupporting
confidence: 56%
“…The HCN and HCO + data are in good agreement with previous measurements (e.g., Nguyen et al 1992). The gas disk in M82 is known to house two giant photodissociation regions (PDRs; e.g., García-Burillo et al 2002) and probably also a central massive black hole in formation (e.g., Matsushita et al 2000;Patruno et al 2006) and a superbubble emerging from a past SNE (e.g., Wei% et al 1999;Kronberg et al 1985). A different gas chemistry could hence be at play in the center than in the two PDRs.…”
Section: M82: Sb-dominated Galaxymentioning
confidence: 99%
“…X-ray observations have revealed the presence of intermediatemass black holes with masses of 10 3 -10 6 M in M82 (Matsumoto et al 2001;Kaaret et al 2001), whose locations were found to coincide with the star clusters found by SUBARU observations (T. Harashima et al 2002, in preparation). In addition, a very energetic expanding molecular superbubble has been discovered (Matsushita et al 2000). These findings have created a lot of interest in the formation of black holes of various masses and the evolution of starburst galaxies (e.g., Ebisuzaki et al 2001).…”
Section: Introductionmentioning
confidence: 99%